Characterization of patients at high risk of melanoma in Austria3. (26th April 2016) - Müller, C.; Wendt, J.; Rauscher, S.; Burgstaller‐Muehlbacher, S.; Sunder‐Plassmann, R.; Scheurecker, C.; Richtig, E.; Fae, I.; Fischer, G.; Pehamberger, H.; Okamoto, I.
Summary: Background: Risk of melanoma is determined by genetic and exogenous factors. Only a few studies have included both characteristics in a comprehensive multivariable analysis. Objectives: To find determinants of patients at high risk of melanoma in Austria, including phenotype, genotype and lifestyle characteristics in comprehensive analyses. Methods: In total, 1668 patients with melanoma from the M3 case–control study were studied. Overall, 567 participants were sequenced for CDKN2A, 232 for CDK4, 123 for MITF encoding the variant E318K and 964 for MC1R . Results: Patients with melanoma with a positive family history ( n = 190, 11·6%), multiple primary melanomas ( n = 261, 15·7%) and younger age (< 50 years, n = 675, 40·5%) were defined as being at high risk. All other patients with melanoma were defined as the reference group. We found significant differences between those two groups and between the high‐risk subgroups (positive family history, multiple primary melanomas and younger age). Pigmentation phenotype was associated with the high‐risk group in general (childhood freckling, odds ratio 1·46, P = 0·007; blond/reddish hair colour, odds ratio 1·43, P = 0·011). Patients with a positive family history and patients with early‐onset disease were similar regarding both their phenotypic characteristics and external factors. Established high‐risk mutations in CDKN2A were found in cases with a positive family history ( n = 12) or multiple melanomas ( n = 2). Moreover, we found three patients carrying the MITF p.E318K variant, two with a CDK4 variant and seven with nonsynonymous MC1R variants with undescribed biological significance, of which four were predicted as damaging. Conclusions: Austrian patients could represent a reservoir for novel genetic variants. Further investigation of populations in Central and Eastern Europe might reveal more novel and disease‐relevant variants. Abstract : What's already known about this topic? Melanoma risk is determined by environmental and genetic risk factors. The frequency and type of disease‐causing gene mutations vary between different countries. What does this study add? This is the first comprehensive description of Austrian patients at high risk of melanoma. The heterogeneity of the different subgroups suggests diverse pathways. We present functional prediction of MC1R and CDK4 variants with unknown biological significance in high‐risk patients, and three novel cases with MITF variants in high‐risk patients. What is the translational message? Identification of high‐risk individuals helps to reduce mortality. The risk of melanoma is comprised of a complex interplay between genetic and environmental factors; however, genetic mutations associated with melanoma might differ from country to country. Knowledge of these mutations and adjustment of criteria for testing could be required for adequate risk assessments. Linked Comment: Stefanaki and Stratigos. Br J Dermatol 2016;174: 1188–1190 . Plain language summary available online